Effectiveness of CO2 laser on urogenital syndrome in women with a previous gynecological neoplasia: a multicentric study. Issue 5 (27th March 2020) - Angioli, Roberto; Stefano, Salvatore; Filippini, Maurizio; Pieralli, Annalisa; Montera, Roberto; Plotti, Francesco; Gatti, Alessandra; Bartolone, Martina; Luvero, Daniela
Abstract : Background: Many women diagnosed with gynecological cancers undergo adjuvant therapy, which may lead to transient or permanent menopause that ultimately leads to urogenital syndrome and vulvovaginal atrophy. Studies advise against the use of estrogen in women with a history of hormone-dependent cancer. One alternative is vaginal microablative fractional CO2 laser, which promotes tissue regeneration through the production of collagen and elastic fibers. Objective: To evaluate the effectiveness of CO2 laser in the treatment of urogenital syndrome—in particular, symptomatic vulvovaginal atrophy in women who have survived gynecological cancers. Methods: A retrospective study was carried out, including all patients with a history of gynecological cancers and vulvovaginal atrophy who underwent CO2 laser treatment between November 2012 and February 2018 in four Italian centers. The study was approved by the local ethics committee of each participating institution. The inclusion criteria were women aged between 18 and 75; Eastern Cooperative Oncology Group performance status <2; and history of breast, ovarian, cervical, or uterus cancer. Patients had to have vulvovaginal atrophy and at least one of the following symptoms of urogenital syndrome: vaginal dryness, dyspareunia, vaginal introitus pain, burning, or itching. Three applications were administered at baseline, 30 days, and 60 days. All patients were evaluated before the first laser session, at each session, and 4 weeks after the last session. In particular, patients were asked to indicate the intensity of symptoms before the first session and 4 weeks after the last session, using Visual Analog Scale (VAS) scoring from 0 ('no discomfort') to 10 ('maximum discomfort'). Results: A total of 1213 patients underwent CO2 laser treatment and of these, 1048 were excluded because they did not meet the inclusion criteria in the analysis. Finally, a total of 165 patients were included in the study. The mean age at the time of treatment was 53 years (range 31–73). Dryness improved by 66%, dyspareunia improved by 59%, burning improved by 66%, pain at introitus improved by 54%, and itching improved by 54%. The side effects were evaluated as pain greater than VAS score 6 during and after the treatment period. No side effects were seen in any sessions. Conclusions: Fractional microablative CO2 laser therapy offers an effective strategy in the management of the symptoms of genitourinary syndrome in post-menopausal women and in survivors of gynecological cancer.